THE INFLUENCE OF HRM PRACTICES ON MANUFACTURING PERFORMANCE IN MALAYSIAN MANUFACTURING FIRMS - AMIN, BOKHORI MD (International Journal of Multidisciplinary Research and Studies, 2020)
This study evaluated the relationship between compensation and performance, training and performance, and recruitment and performance on manufacturing' performance in manufacturing firms in Penang, Malaysia. A sample size of 222 respondents was taken from 28 electrical manufacturing firms with a 6322 population and 361 samples to examine the relationship. A questionnaire was designed for data collection to measure compensation and performance, training and performance, and recruitment and performance on employees' performance in manufacturing firms. A stratified sampling method was used, and the data was analyzed using SmartPls 3.7.8. The study showed that compensation and performance, training and performance, and recruitment and performance have a significant relationship with manufacturing' performance in manufacturing firms. However, the limitation of this study only covers electrical manufacturing firms. Suggested for future study focus on electronic, plastic, and fabricated manufacturing firms to be more effective in improving manufacturing firms' performance.